Hubungan Ilmu Komunikasi dengan Ilmu Lain - Efendi, Erwan; Al Azra, Abdi; Afidah, Rafiatul; Putri, Hentina; Ramadan, Gilang; Amelia, Sopy (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The findings of the study demonstrate that, ontologically speaking, Islamic communication science is a branch of da'wah, the science that aims to disseminate genuine and true Islamic knowledge, concepts, and viewpoints. The individualism-conformity, egalitarian-hierarchical, transcendatalism-existentialism, and intuitive rational processes paradigms are then applied by Islamic communication science. Its epistemological foundations are amanah, taqwa, ummah, amar ma'ruf nahi munkar, and monotheism. The techniques employed, especially the bayani, tajribi, burhani, and irfani techniques, still make reference to Islamic epistemology. Additionally, axiologically, Islamic communication science is based on morals and values found in the Qur'an and Hadith. It seeks to advance Islamic communication theory, solve communication issues between people, and serve as a human medium for enhancing self-worth and developing human curiosity about science.